All the wilderness [videorecording (DVD)] - Johnson, Michael; Smit-McPhee, Kodi; Madsen, Virginia, 1961-; Fuhrman, Isabelle, 1997-; DeVito, Danny (Screen Media Films, 2015)
Following the death of his father and faced with being sent off to boarding school, James learns about life and himself as he meets up with two mysterious teens and experiences the Portland underground music scene.